Bagaimana Lingkungan Kota Memengaruhi Kebahagiaan Anak? Sebuah Tinjauan Pelingkupan - Arlinkasari, Fitri; Kusristanti, Chandradewi; Putra, Johan Satria (ANIMA Indonesian Psychological Journal, 2025)
Child-Friendly City Initiatives (CFCI) emphasizes the importance of creating urban environments that support children’s health and well-being. This scoping review maps studies that examine the relationship between urban environmental characteristics and children’s happiness (well-being) with children as participants. Based on a systematic search of four databases (Web of Science [WoS], SAGE Journals, Scopus, and ProQuest), eight articles were identified that met the inclusion criteria, namely: (a) empirical studies involving children’s perspectives; (b) studies examining the relationship between urban environmental features and children’s happiness (well-being); and (c) studies published in peer-reviewed English-language journals between 2004-2024. This scoping review revealed that there are five main environmental features that influence children’s happiness (well-being), namely: (1) built environment; (2) natural environment; (3) play areas; (4) traffic conditions; and (5) cohesive social environment. These features influence children's happiness (well-being) through three underlying mechanisms, namely: (1) psychological; (2) social; and (3) physical activity. Moderating factors such as age, socioeconomic status, and gender identity were also identified as influencing the strength of the relationship between environmental features and children's happiness (well-being). This scoping review also produces recommendations for future study directions to enrich the understanding of the relationship between urban environments and children's happiness (well-being) in urban areas.